Plant and animal ways - Podendorf, Illa. (Chicago, Ill. : Child's World, 1971)
Discusses the characteristics of a representative sample from the world's wide variety of animals and plants.
Includes index.
Keywords: Animals -- Juvenile literature; Plants -- Juvenile literature